A Concise Guide to Lecturing in Higher Education and the Academic Professional Apprenticeship - Hindmarch, Duncan; Machin, Lynn; Murray, Sandra; Richardson, Tina; Walmsley-Smith, Helen (Routledge, 2020)
Ideal for lecturers new to delivering higher education in universities, colleges and the private sector. It is specifically organised to cover the requirements of the new Academic Professional Apprenticeship, both teaching and research specialisms, and also supports lecturers undertaking the Post Graduate Certificate in Higher Education. The contents are fully mapped to the Higher Education Academy's UK Professional Standards Framework and the VITAE research standards. It is designed for both teaching and research lecturer apprenticeship routes and includes clear guidance to help pass the end-point assessment. There is a focus on the holistic development of the academic professional within the current context of higher education.